Alternative animal model for Pasteurella multocida and Haemorrhagic septicaemia - Hussaini, J.; Nazmul, M.H.M.; Masyitah, N.; Abdullah, M.A.; Ismail, S. (Biomedical Research Press, 2013)
A suitable animal model is essential in understanding a condition caused by microorganisms. In this study in order to study the changes in haemorrahgic septicaemia caused by Pasteurella multocida serotype B, Sprague-Dawley (SK/WDY) rats were immuo-suppressed with dexamethasone and challenged with P.multocida serotype B:2. The animals were monitored/inspected twice daily. Any changes in behaviour, movement, eating and development of any signs and symptoms were recorded. Immune-suppressed rats showed signs of haemorrahge and lesion in the lungs.